Comparative efficacy and safety of transarterial treatment strategies for hepatocellular carcinoma: a systematic review and network meta-analysis of randomized controlled trials - Jiajun Chen; Ganfa Huang; Fengyi Mo; Zijun Liao; Chang Zhao (Frontiers in Medicine, 2026)
Background Transarterial therapy is widely used for unresectable or intermediate-stage hepatocellular carcinoma (HCC), but the comparative efficacy and safety of available techniques remain uncertain. We compared the efficacy and safety of conventional TACE (cTACE), drug-eluting bead TACE (DEB-TACE), degradable starch microsphere TACE (DSM-TACE), balloon-occluded TACE (B-TACE), transarterial embolization (TAE), and transarterial radioembolization (TARE). Methods We performed a PROSPERO-registered systematic review and network meta-analysis of randomized controlled trials. PubMed, Embase, Web of Science, CENTRAL, and CNKI were searched from inception to May 1, 2026. The primary efficacy outcome was objective response rate (ORR). Random-effects network meta-analysis was used. Risk of bias was assessed with RoB 2, and certainty of evidence with CINeMA. Results Fifty-six randomized trials involving 5,083 patients were included; 48 trials (4,282 patients) contributed to the ORR network. B-TACE yielded an ORR risk ratio (RR) of 3.50 versus cTACE (95% CI 1.92–6.36, p < 0.001), but this estimate arose from three small trials, so is hypothesis-generating. DEB-TACE improved ORR versus cTACE (RR 1.36, 95% CI 1.27–1.47, p < 0.001). The TARE estimate was compatible with no effect (RR 1.23, 95% CI 0.98–1.53, p = 0.069). DEB-TACE was associated with less nausea or vomiting (cTACE vs. DEB-TACE: OR 1.58, 95% CI 1.19–2.11, p = 0.002), abdominal pain (OR 1.55, 95% CI 1.08–2.22, p = 0.017), and fever (OR 1.47, 95% CI 1.12–1.93, p = 0.006). Conclusion Among currently available randomized evidence, DEB-TACE showed the most consistent overall benefit compared with cTACE, improving tumor response while reducing common post-embolization symptoms. The apparently large B-TACE ORR effect should be considered hypothesis-generating because it is based on sparse, clinically indirect evidence. Comparisons of DSM-TACE, B-TACE, TAE, and TARE with cTACE remain insufficient to establish a definitive overall advantage. Systematic review registration PROSPERO registration: CRD420261392214.